SIFAT DAN KUALITAS GAHARU (GONYSTILLUS SPEC.) - Tjutju Nurhayati Syahri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Gaharu of Gonystillus spec. from South Kalimantan has the following properties : moisture content 5%, essential oil content 51%, caloriffic value 5655 cal/g, ash content 0.24%, and specific gravity 0. 76. According to the quality clasifi cation, the gaharu of Gonystillus spec. belong to no. I - b, and its sales was Rp. 250,000.-Lignin content of gaharu was about the same as lignin content of wood, cellulose and pentosan are somewhat lower.It was meant that lignin was not be degradated, but cellulose and pentosan was degradated by fungi in the production of gaharu.